2018
DOI: 10.1155/2018/5037912
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Wound Healing and Anti‐Inflammatory Activities of Leaf Latex of Aloe megalacantha Baker (Xanthorrhoeaceae)

Abstract: Background Aloe megalacantha Baker (Xanthorrhoeaceae) is one of the Aloe species widely distributed in Ethiopia. The leaf latex of the plant is used for treatment of wounds, inflammation, and other multiple ailments in Ethiopian traditional medicine. Purpose The aim of this study was to evaluate in vivo wound healing and anti-inflammatory activities of the leaf latex of Aloe megalacantha in mice. Methods The wound healing activity of the leaf latex of the plant was studied topically by incorporating the latex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…Previous studies have described contraction in mice as a common physiological phenomenon after skin grafting. Park et al (2014) compared the use of splinted versus non-splinted models and demonstrated that the wound generated in the skin of the animal tends to fully shrink and contract after 11 d in non-splinted models, whereas splinted models reduce the contraction rate to near 60 % after 11 d (Gebremeskel et al, 2018;Park et al, 2014). In the present study, the wound contraction percentage reached 61.7 % after 30 d, suggesting a reduction of the wound contraction that may improve re-epithelisation with the grafted tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described contraction in mice as a common physiological phenomenon after skin grafting. Park et al (2014) compared the use of splinted versus non-splinted models and demonstrated that the wound generated in the skin of the animal tends to fully shrink and contract after 11 d in non-splinted models, whereas splinted models reduce the contraction rate to near 60 % after 11 d (Gebremeskel et al, 2018;Park et al, 2014). In the present study, the wound contraction percentage reached 61.7 % after 30 d, suggesting a reduction of the wound contraction that may improve re-epithelisation with the grafted tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the people of Sidama utilized the leaf of Aloe megalacantha for the management of tuberculosis [ 18 ]. In vivo and in vitro studies of the leaf exudate of Aloe megalacantha also revealed significant antimalarial [ 19 ], wound healing, anti-inflammatory [ 20 ], antidiabetic, and antihyperlipidemic activities [ 21 , 22 ]. Numerous compounds isolated from the roots of this plant also displayed cytotoxic effects [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia there are around 46 species of Aloe, of which about 66% are endemic in the country [8]. Several of these endemic species possessed different biological activities, including antimicrobial [9,10], antitrypanosomiasis [11], antileishmaniasis [12,13], antimalarial [14][15][16], wound healing [17], anti-inflammatory [17,18], anticancer [19], antidiabetic [20], and antioxidant activities [21]. is relevance indicates that Aloe is the store house of numerous bioactive compounds [22].…”
Section: Introductionmentioning
confidence: 99%